Akselerasi Kinerja Bisnis UMKM di Kecamatan Kendal Melalui Pemanfaatan Teknologi Digital Payment (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2026)
The rapid acceleration of financial technology has shifted the operational paradigm of micro, small, and medium enterprises (MSMEs). This study investigates the impact of digital payment adoption on the business performance of MSMEs in Kendal District. Employing a quantitative approach, data were collected from 100 MSME owners across various sectors, predominantly from the trade, services, and culinary industries. Data analysis was performed using multiple linear regression and partial hypothesis testing (t-test) via SPSS. The findings reveal that digital payment usage exerts a positive and significantly and substantial influence on MSME performance, with a coefficient of determination (R2) reaching 94.5%. Specifically, the integration of digital transactions, led by QRIS (49%), has successfully accelerated sales volume, enhanced transaction speed, and elevated customer satisfaction. Beyond technical efficiency, this study highlights a cultural shift in Kendal’s local economy, where digital tools act as a "leverage" to overcome traditional barriers such as manual bookkeeping and cash-handling risks. However, structural challenges remain, particularly regarding merchant discount rates (MDR) and the lingering dominance of cash among local consumers. These results imply that for MSMEs to remain competitive in a cashless society, stakeholders must prioritize digital literacy and affordable financial infrastructure. This research reinforces the Resource-Based View (RBV) theory, suggesting that digital payment capability is a strategic asset essential for business resilience and sustainable growth in the digital era.